2011
DOI: 10.1007/s12975-010-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

An Insult-Inducible Vector System Activated by Hypoxia and Oxidative Stress for Neuronal Gene Therapy

Abstract: Gene therapy has demonstrated the protective potential of a variety of genes against stroke. However, conventional gene therapy vectors are limited due to the inability to temporally control their expression, which can sometimes lead to deleterious side effects. Thus, an inducible vector that can be temporally controlled and activated by the insult itself would be advantageous. Using hypoxia responsive elements (HRE) and antioxidant responsive elements (ARE), we have constructed an insult-inducible vector acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Cheng and colleagues designed a damage-induced vector system which included a hypoxia response element and an antioxidant response element, which could be activated under oxygen deprivation conditions or upon hydrogen peroxide treatment. The advantage of overexpressing Nrf-2 using this vector system to exert neuroprotective effects is that it activates the expression of neuroprotective genes in the nervous system under hypoxia and oxidative stress [ 187 ]. Research into a HO-2 (heme oxygenase 2) knockout mouse model with ICH induced by autologous blood injection found that, 4–8 days after ICH, neuron survival in the mice was significantly increased, with a reduction in neuromotor deficits.…”
Section: Antioxidant Therapy After Ichmentioning
confidence: 99%
“…Cheng and colleagues designed a damage-induced vector system which included a hypoxia response element and an antioxidant response element, which could be activated under oxygen deprivation conditions or upon hydrogen peroxide treatment. The advantage of overexpressing Nrf-2 using this vector system to exert neuroprotective effects is that it activates the expression of neuroprotective genes in the nervous system under hypoxia and oxidative stress [ 187 ]. Research into a HO-2 (heme oxygenase 2) knockout mouse model with ICH induced by autologous blood injection found that, 4–8 days after ICH, neuron survival in the mice was significantly increased, with a reduction in neuromotor deficits.…”
Section: Antioxidant Therapy After Ichmentioning
confidence: 99%
“…An in vitro study on primary cortical cultures has recently shown that prolonged expression of the transcription factor NF-E2-related factor 2 (Nrf2) induced by hypoxia and oxidative stress acts neuroprotectively against oxygen glucose deprivation. By inserting the Nrf2 gene in an inducible gene construct, a controlled, neuroprotective effect can be achieved by overexpressing Nrf2 not only during hypoxia but also after reperfusion [ 139 ].…”
Section: Targets Of Therapy In Neuropsychiatric Disordersmentioning
confidence: 99%
“…Recently, hypoxia-specific gene regulatory systems have been developed in animal models to treat ischemia-associated diseases, such as tumor, ischemic myocardium and stroke (Shibata et al, 2000;Su et al, 2002Su et al, , 2004Shen et al, 2006Shen et al, , 2008Su and Kan, 2007;Shi et al, 2009;Cheng et al, 2011). In these systems, HIF-1 works as a trigger to switch on the expression of the therapeutic genes by combining with multiple copies of HRE.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to develop a strategy to conditionally express the therapeutic gene under hypoxia. Recently, multiple copies of hypoxia-responsive elements (HRE) have been employed to regulate the expression of therapeutic genes to cure tumor, ischemic myocardium and stroke (Shibata et al, 2000;Su et al, 2004;Shen et al, 2008;Cheng et al, 2011). Hypoxia-inducible factor-1 (HIF-1) is a transcription factor that plays a key role in the regulation of gene expression under the hypoxic condition (Semenza, 2003).…”
Section: Introductionmentioning
confidence: 99%